Echocardiographic right heart study in patients with chronic obstructive pulmonary disease - Hirachan, Anish; Maskey, Arun; Shah, Ram Kishore; KC, Bishal; Shareef, Miqdhaadh; Roka, Madhu; Manandhar, Reeju; Sherpa, Kunjang; Pandey, Rabindra; Yadav, Dharmanath; KC, Man Bahadur; Sharma, Deewakar (Nepalese Heart Journal, 2017)
Background and Aims: Chronic obstructive pulmonary disease (COPD) is highly prevalent in the Nepalese population. It is associated with significant extrapulmonary effects among which cardiovascular complications are most common. Echocardiography evaluation mainly focused on effects on the right heart function is a salient tool to evaluate the presence of degree of pulmonary hypertension and also identify those group of patients who need more early aggressive therapy for the underling lung disease . We aimed to prospectively study the patients with diagnosed COPD with echocardiogram for evaluating the right heart. Methods: An observational, cross sectional study was done on 50 patients with COPD who were admitted at Bir Hospital and underwent echocardiographic evaluation from Dec 2015 –Dec 2016. All echocardiogaphic parameters focused on right heart and its function were assessed . Results: Out of total 50 COPD patients studied, majority of them were female (32 patients. 64%). The mean age group of the studied patients was 60.9 ±11.4 years. Pulmonary hypertension defined as sPAP>30 mmHg was evident in all of the patients ; with 30 patients (60% ), 14 (28 %) and 6(12 %) patients having severe, moderate and mild pulmonary hypertension respectively. RV dysfunction was evident with reduced average TAPSE values (1.59± 0.38 cm) and elevated RIMP values (0.58±0.16). Conclusion: Majority of COPD patients had evidence of pulmonary hypertension. Echocardiogram can be a helpful tool to assess early changes on the right heart size and function in patients with COPD and also monitor these patients for rapid progression of the illness. Nepalese Heart Journal 2017; Vol 14(2), 9-12